Optimal aspiration pressure of suction pump for oocyte retrieval in infertile patients undergoing in vitro fertilization - Sung Woo Kim; Hye Yun Kim; Ji Yeon Han; Hoon Kim; Seung-Yup Ku (PLoS ONE, 2025)
Background The oocyte retrieval is a critical step in assisted reproductive technologies, including in vitro fertilization and fertility preservation. Despite evolving techniques, the optimal aspiration pressure during retrieval remains debatable, with limited in vivo human studies. Existing studies, primarily in vitro and on animals, suggest that inappropriate aspiration pressures can impair oocyte quality. This study aims to compares the effects of two different aspiration pressures, 120mmHg and 150mmHg, on oocyte recovery, damage, and subsequent embryo development and pregnancy outcomes in infertile women undergoing transvaginal ultrasound-guided oocyte retrieval. Methods and findings This retrospective study analyzed data from 891 women at Seoul National University Hospital between May 2018 and August 2023. A total of 400 cycles were included, with 202 at 120 mmHg and 198 at 150 mmHg aspiration pressures. The primary outcomes were the number of retrieved, matured, fractured oocytes, embryos, and good-grade embryos. Pregnancy outcomes were evaluated by comparing the clinical pregnancy rates and live birth rates. Univariate and multivariate logistic regression analyses were conducted to evaluate the relationship between aspiration pressure, clinical pregnancy, and live birth rates. There was statistically significant difference in the number of retrieved oocytes and mature oocytes between the 120 mmHg group and the 150 mmHg group (6.3±5.2 vs. 7.7±6.7, p = 0.018; 4.4±3.7 vs. 5.6±5.3, p = 0.011). The number of embryos and good grade embryos also differed significantly (3.3±3.1 vs. 4.2±3.9, p = 0.011; 1.0±1.6 vs. 1.5±2.6, p = 0.031). However, there were no significant differences in clinical pregnancy and live birth rates between the two groups in multivariate logistic regression analysis (adjusted OR = 0.725, p = 0.519; adjusted OR = 0.370, p = 0.170). Conclusions Increasing the aspiration pressure to 150mmHg led to a higher yield of oocytes and embryos than 120mmHg, without any negative impact on oocyte quality or live birth rates. These findings provide valuable insights for clinical decision-making in infertility treatments, suggesting that 150mmHg may be a more effective pressure for oocyte retrieval in in vitro fertilization and embryo transfer.